2017
DOI: 10.1093/ehjqcco/qcx039
|View full text |Cite
|
Sign up to set email alerts
|

Changes in symptoms of anxiety and depression following diagnostic angiography: a prospective cohort study

Abstract: This study demonstrates that patients with normal coronary arteries or minimal coronary disease/non-obstructive coronary disease do not seem to obtain the same benefit from the receipt of information about their coronary status in terms of anxiety and depression as patients with significant obstructive stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…9,10,20,21 Periprocedural anxiety is a frequent condition both in conventional and computed tomography CAG. [11][12][13]16,22 Although ambivalent results had been obtained in several studies, patients feel more apprehension instantly before the procedure, which remains high at the early postoperative period but decreases gradually in a few months. 11,13,16,23 According to findings of the studies performed by Delewi et al (VAS was used) and Ozdemir et al (Hospital Anxiety-Depression Scale, SSAI, and STAI were used), LOA even increases after the procedure in patients without significant coronary artery lesions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…9,10,20,21 Periprocedural anxiety is a frequent condition both in conventional and computed tomography CAG. [11][12][13]16,22 Although ambivalent results had been obtained in several studies, patients feel more apprehension instantly before the procedure, which remains high at the early postoperative period but decreases gradually in a few months. 11,13,16,23 According to findings of the studies performed by Delewi et al (VAS was used) and Ozdemir et al (Hospital Anxiety-Depression Scale, SSAI, and STAI were used), LOA even increases after the procedure in patients without significant coronary artery lesions.…”
Section: Discussionmentioning
confidence: 96%
“…11,16 Regardless of the results of CAG, the perception of health and quality of life are impaired in this population. 22 Post-operative LOA and relationship of LOA with coronary lesions were not addressed as outcomes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] In addition to adverse clinical outcomes, chest pain with normal angiography can also lead to adverse psychological outcomes. 17 Thinking on ischemia should not be limited to the…”
Section: F O R H Y P E R T E N S I O N P E E R R E V I E W D O N O mentioning
confidence: 99%
“…10,11 Extant literature has been published relating to the prevalence of anxiety in patients undergoing cardiac catheterization using the transfemoral approach. Evidence suggests that between 24% and 72% [12][13][14] of these patients experience high levels of anxiety and psychological distress before the procedure. [15][16][17] Authors of studies measuring anxiety using the State-Trait Anxiety Inventory (STAI) have reported scores between 35.7 points 14 and 43.7 points 18 for patients having cardiac catheterization using the transfemoral approach.…”
mentioning
confidence: 99%